Djibouti : 2014 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Djibouti. (IMF Staff Country Reports; Country Report, 2015)
This 2014 Article IV Consultation highlights that Djibouti is undergoing an investment boom that would accelerate economic growth. Aggregate investment is projected to rise from 26 percent of GDP in 2010-13 to 52 percent in 2014-16. GDP growth is expected to rise from 6 percent in 2014 to about 7 percent in 2015-19. Inflation is projected to pick up from 3 percent in 2014 to 3.3 percent in 2015-19 as the large investment spending fuels demand for housing and basic services. Central bank gross foreign assets are projected to remain strong, permitting full currency board coverage over the period 2015-19.